Diseño de un dispositivo para la movilidad de personas con discapacidad motriz usando el método función de calidad - Bravo, Leonardo Contreras; Granados, Wilmar Augusto (Ingeniería, 2014)
This paper describes the design of a mobility device for physically disabled people between 8-15 years with T12 pathologies and no co-morbidities in the upper limbs. It begins by eliciting the customer’s requirements, and conversion to designs prototypes using a tool called quality function (QFD - Quality Function Deployment). The evaluation of the different designs is also shown. Once the qualitative description is characterized quantitatively, the design process proceeds by systemically generating particular elements to reach the global design by joining the technical elements and requirements of the user. In the fi nal part of the paper, several designs using Solid Edge software are presented. Lastly, the model that better meets customer requirements indicated by the QFD analysis is chosen.